Always a burden? Healthcare providers' perspectives on moral distress. Issue 5 (29th September 2017) - Prentice, Trisha M; Gillam, Lynn; Davis, Peter G; Janvier, Annie
Abstract : Background: Current conceptualisations of moral distress largely portray a negative phenomenon that leads to burnout, reduced job satisfaction and poor patient care. Objective: To explore clinical experiences, perspectives and perceptions of moral distress in neonatology. Design: An anonymous questionnaire was distributed to medical and nursing providers within two tertiary level neonatal intensive care units (NICUs)—one surgical and one perinatal—seeking their understanding of the term and their experience of it. Open-ended questions were analysed using qualitative methodology. Results: A total of 345 healthcare providers from two NICUs participated (80% response rate): 286 nurses and 59 medical providers. Moral distress was correctly identified as constrained moral judgement resulting in distress by 93% of participants. However, in practice the term moral distress was also used as an umbrella term to articulate different forms of distress. Moral distress was experienced by 72% of providers at least once a month. Yet despite the negative sequelae of moral distress, few (8% medical, 21% nursing providers) thought that moral distress should be eliminated from the NICU. Open-ended responses revealed that while interventions were desired to decrease the negative impacts of moral distress, moral distress was also viewed as an essential component of the caring profession that prompts robust discussion and acts as an impetus for medical decision-making. Conclusions: Moral distress remains prevalent within NICUs. While the harmful aspects of moral distress need to be mitigated, moral distress may have a positive role in advocating for and promoting the interests of the neonatal population.